High Improved Glasgow Prognostic Score (iGPS) Predicts Increased Postoperative Mortality in Stage I-III Colorectal Cancer: A Kaplan-Meier Survival Analysis - Gerry Armando; Efman Manawan; Theodorus (Sriwijaya Journal of Surgery, 2025)
Introduction: Colorectal cancer (CRC) represents a formidable cause of cancer-related mortality globally. Accurate prognostication that extends beyond conventional TNM staging is imperative for optimizing patient management. The Improved Glasgow Prognostic Score (iGPS), an inflammation-based biomarker derived from C-reactive protein (CRP) and albumin, has demonstrated considerable promise; however, its clinical utility has not been extensively validated in Southeast Asian populations. This study was therefore designed to investigate the association between preoperative iGPS and postoperative mortality among patients with non-metastatic CRC in an Indonesian tertiary care center. Methods: This study employed an ambispective cohort design, enrolling 33 patients with stage I-III CRC who underwent surgical resection at Dr. Mohammad Hoesin Hospital, Palembang. Preoperative serum CRP and albumin concentrations were utilized to calculate each patient's iGPS, which was then stratified into three risk categories: score 0 (low), 1 (medium), or 2 (high). The primary endpoint was all-cause postoperative mortality. The prognostic significance of iGPS in relation to survival was evaluated using the Kaplan-Meier method and log-rank test. Results: The patient cohort was predominantly composed of individuals aged ≥40 years (90.9%), with a median age of 59. Stage 3B was the most frequently observed pathological stage (39.4%). The overall mortality rate during the observational period was 57.6%. A robust association was identified between iGPS and survival outcomes. The survival probability for patients with iGPS 0 was 100%. Conversely, survival was substantially diminished in patients with iGPS 1 (33.3%) and iGPS 2 (42.1%). Kaplan-Meier analysis revealed a statistically significant divergence in survival distributions (p < 0.05), with higher iGPS scores correlating with markedly inferior survival. Conclusion: The preoperative iGPS is a potent and significant predictor of postoperative mortality in this Indonesian cohort of patients with non-metastatic CRC. Its utility as an accessible, cost-effective, and objective instrument for risk stratification is substantial. The integration of iGPS into routine clinical practice could enhance prognostic accuracy and aid in therapeutic decision-making.